Promoting smoking cessation in Russian Karelia: a 1-year community-based program with quasi-experimental evaluation - McAlister, Alfred L.; Gumina, Tamara; Urjanheimo, Eeva-Liisa; Laatikainen, Tiina; Uhanov, Mihail; Oganov, Rafael; Puska, Pekka (Health Promotion International, 2000)
Cigarette smoking is a major contributor to the East–West health gap in Europe, a situation which is particularly evident in comparisons of mortality and health behavior in Finnish and Russian Karelia. With technical assistance from the North Karelia Project in Finland, a Quit and Win smoking cessation contest was organized in the district of Pitkäranta in Russian Karelia. Local health care workers organized media publicity and community support, including news about competition winners and participants, and distribution of leaflets featuring stories about how local people were able to stop smoking during the Quit and Win contests. The Pitkäranta campaign was evaluated in a quasi-experimental study in which panels of 176 and 202 smokers, identified in a random population sample survey at the outset, were followed for 1 year in Pitkäranta and a comparable neighboring district. Cessation rates were estimated to be 7–26% in Pitkäranta and 1–2% in the comparison area, a statistically significant indication of experimental effects. These findings demonstrate that community campaigns can effectively reduce smoking in the present difficult conditions in Russia.